2019
DOI: 10.26822/iejee.2019248590
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on the Relationship between Reading Fluency and Level of Reading Comprehension According to the Type of Texts

Abstract: The purpose of this study is to investigate the relationship between the reading fluency and the reading comprehension in accordance with the type of the text. Participants of the study are 99 students who were chosen among fifth graders in a Turkish secondary school. The study utilized descriptive analysis and adopted predictive correlational research design. "Reading Comprehension Test" and "Multidimensional Reading Scale" were used as data-collection tools. According to findings; while the speed of reading,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…(Duke, 2000;Li, Beecher, & Cho, 2018). Informational texts may be more difficult to comprehend because of their structural complexity, abstract and logical relations, and domain-specific knowledge (McNamara, Ozuru, & Floyd, 2011), although some research shows no difference in narrative or informational text comprehension (Uysal & Bilge, 2019).…”
Section: Current Studymentioning
confidence: 99%
“…(Duke, 2000;Li, Beecher, & Cho, 2018). Informational texts may be more difficult to comprehend because of their structural complexity, abstract and logical relations, and domain-specific knowledge (McNamara, Ozuru, & Floyd, 2011), although some research shows no difference in narrative or informational text comprehension (Uysal & Bilge, 2019).…”
Section: Current Studymentioning
confidence: 99%
“…Fundamentally, the reading process aims to describe the system in a specific text. Reading is the activity of making sense of what is being read by associating words or phrases in the text within themselves, no matter what state, form, or structure (Uysal & Bilge, 2019). In performing this activity, the reader also reveals the forms and methods of making sense of the text, which are revealed by poetics and text analysis theories.…”
Section: A Connection Must Be Established Between Sentencesmentioning
confidence: 99%
“…Although there are many definitions in this regard, there is debate about which of these definitions is better. Researchers can be said to agree among reading educators that reading comprehension is a multidimensional process (Klein, 1988;Uysal & Bilge, 2019). Akyol, Çakıroglu & Kuryer (2014) in their study it was concluded that for the development of the reading skills of the students having reading difficulty, construction of appropriate reading environment and implementation of enrichment reading programs can be effective.…”
Section: A Connection Must Be Established Between Sentencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reading could be interpreted as an understanding the meaning of printed words. It is an active process which consists of recognition and comprehension skill (Patel & Jain, 2008) and a basic skill for learning at every stage of education process (Kanık & Bilge, 2018). A student's reading skill is essential to learning (Severino, Jean, Decarlo, & Sondergeld, 2018).…”
Section: Introductionmentioning
confidence: 99%